Possibilities and limitations of applying ChatGPT in the educational process - Namesztovszk Zsolt B.; Glušac Dragana R.; Arsović Branka B.; Kovacs Elvira I. (Zbornik radova (Univerzitet u Kragujevcu. Pedagoški fakultet u Užicu))
In recent years, the rise of advanced artificial intelligence technologies has had a profound impact on many fields, including education. One such technology is ChatGPT, a powerful large language model developed by OpenAI. In this paper, the authors consider the possibilities and limitations of applying artificial intelligence, primarily ChatGPT, in the educational process. In addition to general definitions, this popular technology is briefly presented, as well as the possibilities of its application. Consideration is mainly carried out from the educational aspect, with the role of the teacher still in the centre. At the same time, appropriate didactic, pedagogical, and methodical possibilities were presented, with which the teacher can be innovative and even more successful, effectively applying ChatGPT in everyday educational work. Of course, the limitations arising from the application of artificial intelligence are also presented. In this article, the benefits and risks related to the use of ChatGPT in education are discussed. The article argues that ChatGPT has at least five main benefits, such as creating learning assessment, enhancing pedagogical practice, offering virtual personal tutoring, creating an essay or research article outline, and brainstorming ideas. However, there are risks related to academic integrity issues, unfair learning assessment, inaccurate information, and over-reliance on AI. The article offers a set of recommendations for the effective use of ChatGPT for educational purposes. As a final result, we get a more realistic picture of this current topic, which also shows the pedagogical aspects and does not diminish the role of the teacher.